Convict shame to convict chic: Intergenerational memory and family histories. (August 2019) - Barnwell, Ashley
This article highlights the significance of family history research for memory studies. It provides an overview of the economic and cultural impact of this popular practice as well as a survey of the interdisciplinary field of research emerging around questions of genealogy and identity. It then develops a framework for engaging with the intergenerational, socially responsive memory work of family historians drawing from Paul Connerton's typography of forgetting, Maurice Halbwach's theory of social memory and Karl Mannheim's notion of generations. The article grounds this framework with a case study about generational conflicts in Australian family histories, specifically around the shifting status of the convict ancestor, from a figure of secrecy and shame to one of pride and intrigue. I argue that family history research reveals the process by which generations have shaped memory, editing 'the family narrative' in response to changing social ideas about which kinds of identities and families hold value and promise. The names and dates on family trees therefore tell the stories not just of a discrete set of individuals but also of how social, national and generational interests interlink to produce the narratives we live by in both intimate and public spheres.